Postoperative Ascites of Unknown Origin following Laparoscopic Appendicectomy: An Unusual Complication of Laparoscopic Surgery. (13th April 2014) - Feretis, M.; Boyd-Carson, H.; Karim, A.
Abstract : Postoperative ascites is a very rare complication of laparoscopic surgery. Significant iatrogenic injuries to the bowel, the urinary tract, and the lymphatic system should be excluded promptly to avoid devastating results for the patient. In some cases, in spite of investigating patients extensively, no definitive causative factor for the accumulation of fluid can be identified. In such cases, idiopathic allergic or inflammatory reaction of the peritoneum may be responsible for the development of ascites. We present a case of ascites of an unknown origin in a young female patient following a laparoscopic appendicectomy.